2001
DOI: 10.1007/bf02234377
|View full text |Cite
|
Sign up to set email alerts
|

Mucosectomy vs. stapled ileal pouch—anal anastomosis in patients with familial adenomatous polyposis

Abstract: Familial adenomatous polyposis patients with stapled ileal pouch-anal anastomosis have better functional outcome and can avoid temporary diversion. This should be balanced against a 28 percent incidence of adenomas in the anal transitional zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
5
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 11 publications
3
124
5
4
Order By: Relevance
“…Although some authors showed favorable results toward stapled IPAA,5, 9, 12 others reported no benefit or a trend toward higher complications 13, 14. In the present study, the analysis revealed no significant difference in the rates of overall complications or extra‐pelvic complications between stapled and hand‐sewn IPAA.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Although some authors showed favorable results toward stapled IPAA,5, 9, 12 others reported no benefit or a trend toward higher complications 13, 14. In the present study, the analysis revealed no significant difference in the rates of overall complications or extra‐pelvic complications between stapled and hand‐sewn IPAA.…”
Section: Discussioncontrasting
confidence: 53%
“…The authors reported 31% and 23% pouch‐related complications in stapled and hand‐sewn IPAA, respectively. In a consecutive series of 119 restorative TPC for FAP during the period from 1982 to 1999 by Remzi et al.,9 stapled IPAA was introduced from 1988 and finally accounted for 65% of the study population. In Japan, the present data clearly showed that surgeons consistently preferred hand‐sewn IPAA during the study period of 2001‐2012, and stapled IPAA has been conducted rather selectively, although patient characteristics and surgical backgrounds were similar between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations